A systematic review of the changes, challenges, and implications of China’s teacher education policies (2012 to 2023) - Zhi, Huang; Ravindran, Latha; Amini, Mansour (Institute of Advanced Engineering and Science, 2025)
Although China’s teacher education policies have achieved significant progress in improving teacher quality, they have also undergone substantial changes and encountered new challenges. It is necessary to systematically analyze policies from the past decade to achieve a prudent balance between the immediacy and foresight of policymaking. This systematic analysis paper examines China’s teacher education policies from 2012 to 2023, reviewing relevant policy documents from authoritative sources. The study reveals a strategic shift towards fostering comprehensive and innovative teacher talent, promoting professional development, and addressing urbanrural education disparities. Emphasis is placed on strengthening professional ethics and creating a societal atmosphere of respect for teachers. However, challenges arise, including the “de-normalization” of teacher education in higher education institutions, regional disparities in teacher resources, and issues in in-service teacher education. These findings have profound implications for the future of teacher education policies, both within China and globally. They underscore the need for ongoing policy review and adaptation, the importance of balance between research and teaching in teacher education programs, and the need for a more integrated and streamlined approach to in-service teacher education and professional development. The study provides insights for policy development in the field of teacher education.